Evaluation of the Impact of Credit Policy on Financial Performance - Tahu, Gregorius Paulus; Susilo, Dominicus Djoko Budi; Verawati, Yenny (Borong Newinera Publisher, 2025)
This study aims to analyze the impact of credit policy on the financial performance of national banking companies in Indonesia, focusing on how credit policies influence factors such as profitability, financial stability, and liquidity. A quantitative approach is used in this research, with secondary data obtained from published financial reports of national banks, as well as data from the Financial Services Authority (OJK) and Bank Indonesia (BI). The data analysis technique employed is linear regression to examine the relationship between credit policy and financial ratios, including Non-Performing Loans (NPL), Return on Assets (ROA), Return on Equity (ROE), and the Operating Expenses to Operating Income ratio (BOPO) over the period 2015–2022. The results show that the credit policies implemented by banks have a significant impact on profitability, with an average ROA of 2.4% and ROE reaching 12.5%. Moreover, poor credit risk management was found to increase the NPL ratio to 3.2% and lower the banks’ financial performance. Meanwhile, a positive relationship between sound credit risk management and bank liquidity can be observed through the BOPO ratio, which stands at around 75%, indicating operational efficiency. Based on these findings, it is recommended that banks improve their credit risk policies to enhance their performance and financial stability.